Att flytta till särskilt boende. : Äldres upplevelser av transition, timing och relationer. - Arvidsson, Linda (Lunds universitet, Socialhögskolan, 2025)
More than 80,000 people live in nursing homes in Sweden. The move is often the final relocation in life and may involve both psychological and physical strain, with risks of depression, deteriorating health, and premature death. Only individuals with extensive care needs are granted placement, and by law, the move cannot be made against the will of the older person. Despite increased frailty, individuals are thus expected to take significant responsibility for the relocation process themselves. This study explores how older people experience the move to a nursing home, with a particular focus on the role of social relationships. The research is based on a unique dataset comprising 21 interviews, in which seven individuals (aged 87–95) were interviewed during different phases of the relocation process. Article 1 highlights older people’s perspectives on the move and their active role in the process. Drawing on Dorothy Smith’s theory of work, the analysis identifies three forms of work—practical, relational, and emotional—that older individuals engage in during the transition. The results emphasize the importance of considering the entire relocation process, rather than focusing solely on experiences before or after the move, in order to mitigate the negative, stress-related consequences of transitioning to a nursing home. Unlike practical tasks, the older participants’ relational and emotional work was often invisible but demanding. Article 2 aims to deepen understanding of older adults’ experiences of the relocation process, with particular attention to the significance of social relationships throughout the process. By interviewing participants during four distinct phases of the move, the study illustrates three transition trajectories: the insecure transition, the turbulent transition, and the smooth transition. These trajectories show how the relocation process is shaped by relations and timing. Relationships with relatives and care staff proved to be crucial—both as sources of support and sources of concern. Timing also played a central role; a move perceived as “too late” could mean that both the older person and their old, often retired, children were too frail to manage the process. Although legislation emphasizes autonomy, the study 6 shows that relocation must be understood as a relational process shaped by “linked lives” and “unlinked lives” with others. In summary, this study shows that relocation to a nursing home is far more than a physical move, it is an existential, relational, and practical transformation that requires various forms of work. It is a process in which time, timing, support, health, and relationships interact in ways that shape the experience. It is also a process in which the older person is both an agent and dependent, where responsibility and vulnerability coexist. This understanding of relocation as a process rather than a single event has important implications for both policy and practice. It underscores the importance of supporting older people not only practically but also emotionally and relationally, before, during, and after the move. It also points to the need for relocation processes that are flexible, personalized, and better grounded in the lived experiences and needs of older individuals. By viewing relocation to a nursing home as a cohesive, relational, and time-sensitive process, elder care can become more attuned to individual needs. Implementing coordinated support, participatory approaches, and flexible timelines may help preserve the older person’s sense of control and dignity while also reducing the burden on relatives.
Keywords: flytta; transition; äldre; äldre omsorg; äldreboende; särskilt boende; vård; kvalitativ intervjustudie av brukare; kvalitativ metod; tid; relationer; anhöriga; flytt process; samordning; värdighet; delaktighet; transition; relocation; older people; older people care; older people, eldercare, social interaction; residential care; Residential aged care; nursing home; nursing homes; nursing home ethics; nursing home placement